Les paysages de la transition énergétique : une perspective politique - Marie-José Fortin (Projets de Paysage)
Beyond major general objectives, energy transition needs to be translated into concrete policies and projects. The implementation of such policies and projects, often in the form of large sites for the generation of energy, gives rise to strong reactions, notably in defence of the landscape. But rather than interpret this as a reaction of systematic opposition, we propose to consider the landscape as a way of testing the level of territorialisation of proposals made in the name of the energy transition. As a cognitive and political framework, this makes it possible to compare the project with the territory and to understand whether the former is consistent with and able to provide perspectives for the future of the latter. To do so, we propose an analytical framework structured on three levels referring to complementary theoretical approaches: the landscape 1) as a social representation, 2) as a tool and a negotiated object, 3) and as a societal paradigm. The recent wind energy sector in Quebec serves to illustrate how the “landscape” could be mobilised in such a way.